pengaruh product features dan advertising attractiveness terhadap keputusan pembelian honda scoopy tahun 2022 (studi kasus masyarakat di kecamatan tebo tengah) - Yanti, Reni Febri; fenisi resty; kelik purwanto (Jurnal Manajemen dan Bisnis Kreatif, 2023)
Astra Honda Motor Factory issued a Honda Scoopy in 2022 with product sophistication that makes the public interested in buying it. This research was conducted to determine the effect of product features and advertising attractiveness partially and simultaneously on the purchase decision of Honda Scoopy in 2022. This study used quantitative research methods with data collection using questionnaires conducted from May to June with a sample of 366 respondents. The data analysis techniques used are validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, correlation analysis, t tests, f tests and determination tests (R2). The results of this study show that the product features variable partially has a positive and significant effect on the purchase decision which is shown by the results of processing large calculated t value data from the t table (8,948>1.649) and the level of significance value smaller than alpha (0.00<0.05), which is shown by the results Processing large calculated t value data from the T table (10.852>1.649) and significance value levels smaller than Alpha (0.00<0.05), Product Features and Advertising Attractiveness variables simultaneously have a positive and significant effect on the purchase decision which is shown by the results of data processing Calculated F value greater than the F value of the table (310.283>2.630) and the large significance level of Alpha (0.00<0.05), R2 value of 0.643 which means that all independent variables can affect the dependent variable by 64.3% while the remaining 35.7% are influenced by other factors not tested in this study.